The acceptability of layoffs and pay cuts: comparing North America with Germany - Knut Gerlach; David Levine; Gesine Stephan; Olaf Struck (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
Substantial evidence shows that North Americans are generally more accepting of the market than Europeans and attribute market outcomes to a larger degree to effort or skill. This article discusses the perceived fairness of layoffs and pay cuts in North America and Germany. We expect North Americans to be more accepting of layoffs and pay cuts than Germans and that procedures and conditions under which pay cuts or layoffs occur have a stronger impact on fairness perceptions for Germans than for North Americans. This hypothesis is tested using a quasi-experimental design. The empirical results are in line with our considerations.
Keywords: M51; M52; J63; J31; J33; P52; 330; Entlassungen - Akzeptanz; Lohnsenkung - Akzeptanz; institutionelle Faktoren; gesellschaftliche Einstellungen; Gerechtigkeit; soziale Wahrnehmung - internationaler Vergleich; Einkommensunterschied; psychische Faktoren; Arbeitsbeziehungen; soziale Normen; soziale Einstellungen; USA; Bundesrepublik Deutschland; Kanada; Nordamerika; Silicon Valley; Toronto